2010
DOI: 10.7589/0090-3558-46.2.488
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-Year Study of South Australian Dolphins Shows Variation in Lung Nematodes by Season, Year, Age Class, and Location

Abstract: ABSTRACT:Between 1990 and 2007, carcasses of opportunistically collected short-beaked common dolphins (Delphinus delphis; n5238), Indo-Pacific bottlenose dolphins (Tursiops aduncus; n5167), and common bottlenose dolphins (Tursiops truncatus; n515) were examined for parasites and life history data. Three species of lung nematodes (Halocercus lagenorhynchi, Stenurus ovatus, Pharurus alatus) were identified in surface nodules, subsurface lesions, or airways. Nematode burdens were light to heavy and, in many cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…The present study also supports this possibility. Such vertical transmission has also been suspected during H. lagenorhynchi infection of the bottlenose dolphin ( Tursiops truncatus ) [8, 10] and the common dolphin ( D. delphis ) [35]. If the vertical transmission hypothesis is true, it is strange that H. pingi is almost not found in >110 cm porpoises.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also supports this possibility. Such vertical transmission has also been suspected during H. lagenorhynchi infection of the bottlenose dolphin ( Tursiops truncatus ) [8, 10] and the common dolphin ( D. delphis ) [35]. If the vertical transmission hypothesis is true, it is strange that H. pingi is almost not found in >110 cm porpoises.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the prevalence of lungworm infections was determined to be 77% in the stranded bottlenose dolphins [15] . To date, Stenurus ovatus, Halocercus lagenorhynchi, Pharurus alatus, and Skrjabinalius cryptocephalus related verminous pneumonia [1,15,16] was reported in the bottlenose dolphins; but there was no case related to S. minor. It is reported that the prevalence of S. minor infection of harbor dolphins on the coast of Norway, Iceland, Greenland and South America was 66-100% [17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…However, little information is known about the role parasites in the deaths and strandings of dolphins [1] . Lungworms (Metastrongyloidea: Pseudaliidae) have been implicated as the main factor of natural mortality of dolphins [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the parasites of phocids (seals and sea-lions) have been further investigated, primarily due to pup mortality caused by the hookworm Uncinaria sanguinis (see Marcus et al 2014), while the potential pathological impact of the lungworms Parafilaroides normani and the gastric ascaridoid Contraceacum ogmorhini remain to be determined (Arundel 1978;Nicholson and Fanning 1981;Ladds 2009). There has been little published on the parasites of cetaceans apart from a study of the lungworms of dolphins and their pathological significance (Tomo et al 2010). A review of the helminth parasites causing disease in cetaceans, pinnipeds and the dugong has been published by Ladds (2009).…”
Section: Marine Mammalsmentioning
confidence: 99%